XY (SRY-positive) Ovarian Disorder of Sex Development in Cattle - De Lorenzi, Lisa; Arrighi, Silvana; Rossi, Elena; Grignani, Pierangela; Previderè, Carlo; Bonacina, Stefania; Cremonesi, Fausto; Parma, Pietro (Sexual development, 2018)
In mammals, the sex of the embryo depends on the SRY gene. In the presence of at least one intact and functional copy of this genetic factor (XY embryo) undifferentiated gonads will develop as testicles that subsequently determine the male phenotype. When this factor is not present, i.e., in subjects with 2 X chromosomes, an alternative pathway induces the development of ovaries, hence a female phenotype. In this case study, we describe a female cattle affected by a disorder of sex development (DSD). The subject, despite having a chromosomal XY constitution, did not develop testicles but ovaries, although they were underdeveloped. Moreover, genetic analysis highlighted the presence of the SRY gene with a normal coding region in both blood- and tissue-derived DNA. A chimeric condition was excluded in blood by sexing more than 350 cells and by allele profile investigation of 18 microsatellite markers. Array CGH analysis showed the presence of a not yet described 99-kb duplication (BTA18), but its relationship with the phenotype remains to be demonstrated. Gonadal histology demonstrated paired ovaries: the left one containing a large corpus luteum and the right one showing an underdeveloped aspect and very few early follicles. To our knowledge, we describe the first case of XY (SRY+) DSD in cattle with a normal SRY gene coding sequence.